SARS-CoV-2 infection and complicated appendicitis in adults in Lima, Peru: a matched case-control study - Agustín Mansilla-Sandoval; Diana Corrales-Delgado; Zully M. Puyén; Percy Mansilla-Doria; Edwin Orendo-Velásquez; Luis Huicho; Diego Fano-Sizgorich (BMC Surgery)
Abstract Background Acute appendicitis may be uncomplicated or may present with life threatening complications. Since the outbreak of the COVID-19 pandemic, there has been an increase in the number of cases of complicated appendicitis, suggesting a possible association between them. Therefore, we aimed to determine the association between SARS-CoV-2 infection and complicated appendicitis in surgical patients in Lima, Peru, from March 2020 to December 2021. Methods A matched case-control study was conducted. Clinical records of patients ≥ 18 years old who underwent surgery for appendicitis and had at least one positive SARS-CoV-2 diagnostic test were selected. Patients undergoing surgery for complicated appendicitis were considered cases, and patients undergoing surgery for uncomplicated appendicitis were controls. A 1:1 matching by sex, age, and month of surgery was performed. Conditional logistic regression modeling was performed to calculate crude and adjusted conditional odds ratios (cOR). Results The positivity rate for COVID-19 tests was 73.6% for cases and 26.4% for controls. The crude cOR was 4.88 (95% IC 2.89–8.23, p < 0.001), and the adjusted cOR was 3.52 (95%IC 1.82–6.81, p = 0.001), after controlling for onset time of symptoms and awaiting time before surgery. Conclusions Surgery for complicated appendicitis was associated with SARS-CoV-2 infection. Patients with this infection may be at higher risk of complicated appendicitis and thus may need additional clinical monitoring.